Analisis Dampak Teknologi Pembayaran Digital Terhadap Sistem Transaksi Modern Pengguna Generasi Z - Fadilah Falah Syifa; Mohamad Furqon; Saskiya Azka Safitri Syis Hamidillah (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2026)
The development of digital technology has driven significant changes in the financial transaction system, particularly through the implementation of digital payment technology. One of the innovations that is developing rapidly in Indonesia is the Quick Response Code Indonesian Standard (QRIS), which is designed as a national standard for QR code-based digital payments. This article aims to analyze the mechanism of QRIS technology, the technological factors that drive its adoption among Generation Z, and the positive and negative impacts of its use on modern transaction systems. The research method used is a Systematic Literature Review by examining various scientific articles, official reports, and relevant publications related to digital payment technology and the usage behavior of Generation Z. The results of the study show that QRIS is supported by interoperability technology, an encryption-based security system, and integration with mobile devices that make transactions faster, more practical, and efficient. The characteristics of Generation Z as digital natives with high smartphone usage intensity are the main factors in the high level of QRIS adoption. However, the use of QRIS also presents challenges, such as the potential for increased consumptive behavior, data security risks, and limited digital literacy among some users. Therefore, the development of digital payment technology needs to be balanced with strengthening system security and increasing digital literacy to maximize the benefits of QRIS in supporting modern transaction systems and the national digital economy.